CONTROL OF FOREIGN WORKERS IS CONNECTED WITH THE PROTECTION OF THE WORK RIGHTS UNDER THE CONSTITUTION 1945 AND THE SELECTIVE POLICY PRINCIPLES - Hidayat, Anwar; Budiman,; Widuri Sakti, Intan (International Journal of Psychosocial Rehabilitation, 2020)
The placement of TKA in fact gives an advantage in the process of outsourcing knowledge and technology to improve the skills and productivity of the work of TKI, but the placement of the inappropriate TKA legislation has been detrimental to National interest in the field of employment availability for migrant workers who are increasingly difficult to obtain. The purpose of research to know the control of the TKA is connected with the protection of the job rights for Indonesian citizens according to article 27 paragraph (2) CONSTITUTION 1945, knowing the implementation of foreign workers by TKI in the SCIENCE and find supervision With the selective policy principle. This research uses a normative juridical approach. The specification of the study is descriptive analysis. The data types that secondary data uses. The technique of data collection studies and analytical techniques uses a qualitative approach. The results showed that the control of TKA was executed under Article 42 Law No 13 year 2013 on employment which was built on the principles of legality, sponsorship, selective and security. Controlling the placement of TKA in Indonesia aims to protect the rights of Indonesian citizens for the work pursuant to article 27 sentence (2) CONSTITUTION 1945, but factually the policy of the placement control of TKA has not shown results that provide Protection of the work for Indonesian citizens because of the foreign workers who entered Indonesia majority of the abusive worker without the expertise of non-professional personnel. Supervision of TKA implemented by implementing the principle of selective policy through two approaches namely (a) a prosperity approach that establishes only foreigners who truly benefit the national interests and welfare of the people of Indonesia (b) The security approach of an immigration policy to provide licensing permissions for those who do not compromise state security and public order. Limitation of TKA that will enter Indonesia according to the principle of selective policy becomes a necessity to provide priority position of employment opportunities for TKI.